Eating Disorder Symptoms and Alcohol Use Among Adolescents in Substance Abuse Treatment - Janelle E. Arias; Josephine M. Hawke; Albert J. Arias; Yifrah Kaminer (SAGE Publishing, 2009)
Objective: To examine the relationship of eating disorder (ED) symptoms with the severity of alcohol use among adolescents in treatment for alcohol and other substance use disorders (AOSUDs). Method: A sample consisted of 177 adolescents who participated in outpatient AOSUD treatment programs in Connecticut. Chi square tests, one-way ANOVAs and Pearson's correlation coefficients were used to describe the prevalence and correlates of any eating disorders, and the related symptoms. Multivariate regression was used to test the associations between ED symptoms and alcohol consumption. Results: 26.4% of the participants had at least one ED symptom, with the highest number of symptoms occurring in females. The number of ED symptoms was associated with increases in the number of times that they became intoxicated in the year before entering treatment, the number of alcohol-related social problems, and the number of alcohol-related physical symptoms after taking into consideration the effects of age and gender. Conclusions: The prevalence of symptoms of EDs is high in adolescents with AOSUDs, with the number of ED symptoms correlating with increased alcohol consumption. Further studies on the course and treatment of adolescents with AOSUDs and symptoms of EDs are warranted.